(untitled) (European Journal of Health Research, 2019)
Coping can be defined as the use of cognitive actions or specific behavioral actions to handle difficult and stressful situations, as well as daily problems. On the other hand, previous research shows that mindfulness meditation (MM) can be considered as a means of coping with stressful events in everyday life. The purpose of this study was to measure the effectiveness of a MM program on the coping strategies to manage stress in a population of university students. Randomized controlled study. A sample of sixty-one students from the Faculty of Physiotherapy of A Coruña (Spain) participated in this study. 30 were assigned to a 12 weeks MM program, and 31 were assigned to the control group. The scale of coping strategies (Cabanach, Valle, Rodriguez, Piñeiro, & Freire, 2010), that measures both cognitive and behavioral ways of coping with academic stress, was used. The results indicate that the participants of the experimental group improved their coping strategies after their participation in the program, particularly the positive reappraisal and planning dimensions (a statistically significant difference was observed). In control group there were no pre-post changes. Mindfulness meditation can be an effective method to cope with the stress in university students of Physiotherapy.